A transcription elongation factor that links signals from the reproductive system to lifespan extension in Caenorhabditis elegans. - Arjumand Ghazi; Sivan Henis-Korenblit; Cynthia Kenyon (PLoS Genetics, 2009)
In Caenorhabditis elegans and Drosophila melanogaster, the aging of the soma is influenced by the germline. When germline-stem cells are removed, aging slows and lifespan is increased. The mechanism by which somatic tissues respond to loss of the germline is not well-understood. Surprisingly, we have found that a predicted transcription elongation factor, TCER-1, plays a key role in this process. TCER-1 is required for loss of the germ cells to increase C. elegans' lifespan, and it acts as a regulatory switch in the pathway. When the germ cells are removed, the levels of TCER-1 rise in somatic tissues. This increase is sufficient to trigger key downstream events, as overexpression of tcer-1 extends the lifespan of normal animals that have an intact reproductive system. Our findings suggest that TCER-1 extends lifespan by promoting the expression of a set of genes regulated by the conserved, life-extending transcription factor DAF-16/FOXO. Interestingly, TCER-1 is not required for DAF-16/FOXO to extend lifespan in animals with reduced insulin/IGF-1 signaling. Thus, TCER-1 specifically links the activity of a broadly deployed transcription factor, DAF-16/FOXO, to longevity signals from reproductive tissues.